2014
DOI: 10.3390/cancers6010333
|View full text |Cite
|
Sign up to set email alerts
|

HspB1, HspB5 and HspB4 in Human Cancers: Potent Oncogenic Role of Some of Their Client Proteins

Abstract: Human small heat shock proteins are molecular chaperones that regulate fundamental cellular processes in normal unstressed cells as well as in many cancer cells where they are over-expressed. These proteins are characterized by cell physiology dependent changes in their oligomerization and phosphorylation status. These structural changes allow them to interact with many different client proteins that subsequently display modified activity and/or half-life. Nowdays, the protein interactomes of small Hsps are un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 222 publications
(310 reference statements)
2
73
0
1
Order By: Relevance
“…Molecular biological investigations to study the expression of HSPB1 in tumor tissues and cells from human cancer patients have proved that the expression of HSPB1 is significantly higher in tumor tissues than control tissues from human hepatocellular carcinoma [6] and prostate cancer [4,8,32] and mouse lung cancer [7]. In human hepatocellular carcinoma, HSPB1 stimulates tumor progression through facilitating the hepatocellular carcinoma cells metastasis via Akt signaling [6,22]. Both in vivo and in vitro studies of the prostate cancer indicated that HSPB1 regulates human prostate cancer cell motility and metastatic progression via increased the expression of matrix metalloproteinase 2 (MMP-2) [29], which is a key stimulator for cancer cell invasion [33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular biological investigations to study the expression of HSPB1 in tumor tissues and cells from human cancer patients have proved that the expression of HSPB1 is significantly higher in tumor tissues than control tissues from human hepatocellular carcinoma [6] and prostate cancer [4,8,32] and mouse lung cancer [7]. In human hepatocellular carcinoma, HSPB1 stimulates tumor progression through facilitating the hepatocellular carcinoma cells metastasis via Akt signaling [6,22]. Both in vivo and in vitro studies of the prostate cancer indicated that HSPB1 regulates human prostate cancer cell motility and metastatic progression via increased the expression of matrix metalloproteinase 2 (MMP-2) [29], which is a key stimulator for cancer cell invasion [33].…”
Section: Resultsmentioning
confidence: 99%
“…HSPB1 is one of important components in HSP family [21]. Recent studies have indicated that the expression of HSPB1 is associated with poor prognosis of a wide range of human cancers [20,22], including gastric [23], osteosarcomas [24], prostate [25,26] and liver carcinoma [27]. However, the prognostic roles of HSPB1 in NSCLC have not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…HSPB1 (heat shock protein beta-1) also known as HSP27, plays important roles in cytoprotection, apoptosis, and maintaining normal protein structure during environmental stress. 22 A high level of HSPB1 is a common indicator in CRC, and is usually associated with poorer disease prognosis. [22][23][24] It is also involved in the regulation of cellular stress response, and as an inhibitor of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…22 A high level of HSPB1 is a common indicator in CRC, and is usually associated with poorer disease prognosis. [22][23][24] It is also involved in the regulation of cellular stress response, and as an inhibitor of apoptosis. In fact, the switch between survival and apoptosis in adenocarcinoma cells has been attributed to HSPB1/HSP27.…”
Section: Discussionmentioning
confidence: 99%
“…FABP5, HSPB1, and MnSOD may be potential biomarkers for pelvic lymph node metastasis of cervical cancer, and I-IIst may have an important role in the pathogenesis of pelvic lymph node metastasis (Wang et al, 2014a). Several client proteins with potential pro-cancerous roles have so far been found to interact with HSPB1 and its closely related family members HSPB5 and HSPB4 (Arrigo and Gibert, 2014). Soluble heat-shock protein B1 (HSPB1) is released primarily from endothelial cells and regulates angiogenesis via direct interaction with VEGF.…”
Section: Discussionmentioning
confidence: 99%